AGRICULTURA FAMILIAR E ACESSO AO MERCADO INSTITUCIONAL: Uma análise do Programa Nacional de Alimentação Escolar (PNAE) na Unidade Regional de Educação de São Luís, Maranhão, no período de 2021 a 2024 - GARCIA, Letícia Alaniz (2025)
This dissertation investigates the access of family farmers to the institutional market established within the scope of the National School Feeding Program (PNAE) in the São Luís Regional Education Unit (URE São Luís), which is part of the Maranhão State Department of Education, during the period from 2021 to 2024. Guided by the historical and dialectical materialist method, the study seeks to understand family farming through theoretical debates as well as its current configuration in both the Brazilian and Maranhão contexts. By tracing the history of the school feeding policy, it is demonstrated that the inclusion of family farming results from the recognition of this social segment’s importance, shaped by political mobilizations since the 1990s. Based on the analysis of official documents and field research, the study shows that access to the institutional market under investigation is largely restricted to consolidated formal groups with logistical capacity and transportation. Consequently, the policy fails to encompass the diversity of family farming and requires complementary mechanisms, like agreements among family farmers, in order to achieve less exclusionary outcomes.